Transfer Pricing of Manufacturing Companies in Indonesia - Hikmatin, Rohmah; Suryarini, Trisni (Universitas Negeri Semarang, 2019)
This study aims to analyze the effect of the variables of Tax, Mechanism of Bonuses, Foreign Ownership, and Company Size on Transfer Pricing Transactions in manufacturing companies. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2014-2016. The samples were selected using purposive sampling method and obtained 20 companies or 60 units of analysis which were the object of observation. The technique of data analysis in this research is Partial Regression Analysis with the help of software SmartPLS version 3.0. The results of this study indicate that foreign ownership has a significant affects on transfer pricing transaction. Tax variables, bonus mechanisms, and company size have no significant effect on transfer pricing transactions. As many as four hypotheses submitted only one received, namely foreign ownership has a significant effect on transfer pricing transaction. The conclusions in this study indicate that the higher foreign ownership will affect the transfer pricing transaction. The higher the value of the tax variable, the bonus mechanism, and the size of company does not affect the transfer pricing transaction with the manufacturing companies.